Hari Kiamat dalam Perspektif Hadis - Muhammad Rif'at Farid Jamali; Sholahuddin Al Ayubi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the concept of the Day of Judgment in Islam based on the Prophet Muhammad’s ﷺ hadiths, which serve as primary sources explaining the minor and major signs preceding the end times, providing moral and spiritual guidance for Muslims. Using a qualitative method and library research, authentic hadiths from collections such as Sahih al-Bukhari and Sahih Muslim were thematically analyzed to understand their relevance and moral messages. The findings confirm that the Day of Judgment is an inevitable event preceded by signs meant to warn believers to strengthen their faith and spiritual readiness amid moral decline and the loss of religious knowledge due to the passing of scholars. Friday holds a special status as a sacred day and the time when the Day of Judgment will occur, while certain groups of steadfast and sincere believers will receive Allah’s protection on that day. Overall, these teachings emphasize the importance of maintaining faith, righteous deeds, and Islamic brotherhood as essential preparation for salvation in both this world and the hereafter.